Frailty and Long-Term Post-Kidney Transplant Outcomes - McAdams-DeMarco, Mara A. (Curr Transplant Rep, 2019)
PURPOSE OF REVIEW: To highlight recent research about frailty and its role as a predictor of adverse, long-term post-kidney transplant (KT) outcomes. RECENT FINDINGS: Frailty is easily measured using the physical frailty phenotype (PFP) developed by gerontologist Dr. Linda Fried and colleagues. In recent studies, >50% of KT recipients were frail (20%) or intermediately frail (32%) at KT admission. Frail recipients were at 1.3-times higher risk of immunosuppression intolerance and 2.2-times higher risk of mortality, even after accounting for recipient, donor, and transplant factors; these findings were consistent with those on short-term post-KT outcomes. Pilot data suggests that prehabilitation may be an intervention that increases physiologic reserve in frail KT recipients. SUMMARY: The PFP is a effective tool to measure frailty in ESRD that improves risk stratification for short-term and long-term post-KT outcomes. Interventions to improve physiologic reserve and prevent adverse KT outcomes, particularly among frail KT recipients, are needed.